2016
DOI: 10.1080/1475939x.2016.1217269
|View full text |Cite
|
Sign up to set email alerts
|

Giving up technology and social media: why university lecturers stop using technology in teaching

Abstract: University lecturers use a wide range of technologies when teaching and there has been much research into how particular technologies are adopted. However, there are also many technologies that, despite early promise, are no longer being used in university teaching and have been abandoned by institutions or individuals.This paper presents the results of a qualitative investigation into why university lecturers stop using technology. It used detailed episodic narrative interviews to explore the experiences of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 32 publications
3
29
0
Order By: Relevance
“…Practical barriers eclipse perceived value and restrict usage Findings presented here support previous work which has identified that practical barriers can prevent academics from maximising the advantages of SoMe in their teaching (Manca & Ranieri, 2016a, 2016bRogers-Estable, 2014;Shelton, 2016). While SoMe are considered valuable by educators, there is a shortfall between the proportion of educators who perceive value in SoMe in L&T ( Figure 3A) and those who are actually using it ( Figure 3B).…”
Section: Specific Advantages and A Range Of Approaches And Purposessupporting
confidence: 70%
See 4 more Smart Citations
“…Practical barriers eclipse perceived value and restrict usage Findings presented here support previous work which has identified that practical barriers can prevent academics from maximising the advantages of SoMe in their teaching (Manca & Ranieri, 2016a, 2016bRogers-Estable, 2014;Shelton, 2016). While SoMe are considered valuable by educators, there is a shortfall between the proportion of educators who perceive value in SoMe in L&T ( Figure 3A) and those who are actually using it ( Figure 3B).…”
Section: Specific Advantages and A Range Of Approaches And Purposessupporting
confidence: 70%
“…This highlights the existence of factors that can limit SoMe usage in L&T and also the importance of disseminating the value of SoMe, not only through specific academic conferences and journals and but also through more general sources and practical teaching courses. For example, in terms of time availability, peer-peer SoMe discussions have been described as more effective than those facilitated by the lecturer (Shelton, 2016), a simple practical consideration which may provide an advantage to educators by allowing them to reduce their time involvement in the SoMe-mediated learning process. Some solutions to further barriers described here (Table 2, Figure 4B, 4C) could be addressed through educator training in a workshop situation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations